2016
DOI: 10.1111/psyp.12605
|View full text |Cite
|
Sign up to set email alerts
|

Self‐initiated actions result in suppressed auditory but amplified visual evoked components in healthy participants

Abstract: Self-suppression refers to the phenomenon that sensations initiated by our own movements are typically less salient, and elicit an attenuated neural response, compared to sensations resulting from changes in the external world. Evidence for self-suppression is provided by previous ERP studies in the auditory modality, which have found that healthy participants typically exhibit a reduced auditory N1 component when auditory stimuli are self-initiated as opposed to externally initiated. However, the literature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 44 publications
(81 reference statements)
6
51
2
Order By: Relevance
“…Finally, although we observed numerically larger N1 amplitudes for checkerboards elicited by the dominant hand, resembling the effect reported by Mifsud and colleagues (), the comparison between PV and C‐MI conditions was not significant (similar to the study by Hughes & Waszak, ). This finding was also confirmed by our Bayesian analysis, either suggesting inconclusive evidence for action‐related N1 modulation (Experiment 1) or moderate evidence against such an effect (Experiment 2).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Finally, although we observed numerically larger N1 amplitudes for checkerboards elicited by the dominant hand, resembling the effect reported by Mifsud and colleagues (), the comparison between PV and C‐MI conditions was not significant (similar to the study by Hughes & Waszak, ). This finding was also confirmed by our Bayesian analysis, either suggesting inconclusive evidence for action‐related N1 modulation (Experiment 1) or moderate evidence against such an effect (Experiment 2).…”
Section: Discussionsupporting
confidence: 90%
“…In a very similar vein, Hughes and Waszak () proposed attentional orientation toward self‐generated stimuli as a potential cause for enhanced P1 amplitudes, since this component was shown to be increased for temporally anticipated visual events (Correa, Lupiáñez, Madrid, & Tudela, ; Doherty, Rao, Mesulam, & Nobre, ). Finally, the role of attentional processes was emphasized by Mifsud and colleagues (), observing larger amplitudes for the occipital N145 (rather than for the P1) in their “self‐initiated” condition. However, to control for temporal predictability, these authors also included an experimental condition in which stimulus onset was externally cued to aid the buildup of anticipation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings indicate that action‐related predictive mechanisms might lead to suppression in multiple modalities. However, direct evidence for attenuation of cortical activity in the visual domain is sparse; indeed, some studies have revealed increased visual cortical activity following self‐initiated actions in humans and awake‐behaving mice potentially indicating differential processing of self‐initiated sensory stimuli across modalities.…”
Section: Function Of Sensory Predictionsmentioning
confidence: 99%
“…Specifically, action outcomes are perceived to be attenuated and shifted in time compared to stimuli that are unpredicted or predicted by other stimuli rather than one’s own actions (Von Holst and Mittelstaedt, 1950; Weiskrantz et al, 1971; Blakemore et al, 1998; Haggard et al, 2002). This is a widespread phenomenon that has not only been assessed behaviorally but also neuro-physiologically using different techniques (Schafer and Marcus, 1973; McCarthy and Donchin, 1976; Martikainen et al, 2005; Aliu et al, 2009; Reznik et al, 2014; Timm et al, 2014), including a number of recent EEG studies (Lange, 2011; Desantis et al, 2012; Hughes et al, 2013a,b; SanMiguel et al, 2013; Mifsud et al, 2016; Timm et al, 2016). When outcomes are sounds as in most previous studies, the typical finding are reduced outcome-evoked ERP amplitudes within the latency range of the N1 and P2 components at fronto-central electrodes.…”
Section: Introductionmentioning
confidence: 99%